Sistem Informasi Geografis Pencarian Rute Tercepat Lokasi Penjualan Oleh – oleh khas Lombok dengan menggunakan fungsi WayPoint dan metode Heuristik Greedy Di Kota Mataram Berbasis Web - Anang Nugroho; Wirarama Wedhaswara; Ariyan Zubaidi (Program Studi Teknik Informatika, Fakultas Teknik, Universitas Mataram, 2020)
Abstract- The geographical information system for searching the fastest route of sale location by Lombok specialists using the waypoint function and the heuristic greedy method in the city of Mataram based on web is a web-based Google map mapping application that maps the location of souvenir shops and shop categories especially those located in the city of Mataram . The purpose of making this application is to make it easier for domestic and foreign tourists to search for souvenir shops in Lombok, where tourists can search 1-3 categories of existing stores and search for the closest route from the user's position based on the search category. This system uses the heuristic greedy method for route search, where geolacation is used to get the user's location which is used as a starting location for route search by souvenirs and used as a route by using the waypoint function used to create routes with more than one destination location. The geographic information system for searching the fastest route of souvenir shops in Lombok by using the waypoint function and the heuristic greedy method in the city of Mataram based on the web was created using the CodeIgniter framework with the MVP concept to build web sites. In addition, a Google Map library is needed which functions to display maps on the website created.